1982
DOI: 10.1103/physrevlett.48.867
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Ramsey Fringes Using a Stimulated, Resonance Raman Transition in a Sodium Atomic Beam

Abstract: We report the observation of Ramsey fringes using a stimulated, resonance Raman transition between two long-lived hyperfine ground sublevels, separated by 1772 MHz, in a sodium atomic beam. The observed fringes have a width of 650 Hz [half width at half maximum (HWHM)] for an interaction-region separation of 30 cm which is consistent with transit-time effects in a thermal sodium atomic beam. To our knowledge, these are the narrowest features recorded using optical lasers and have applications in high-re soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
84
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(86 citation statements)
references
References 12 publications
1
84
0
1
Order By: Relevance
“…In recent years, many studies on EIT and related phenomena have been carried out, which reveal the importance of EIT in understanding the fundamental physics involving interactions between light field and resonant medium [4][5][6][7][8]. It has been shown that EIT may have applications in a variety of research topics such as quantum optics with slow photons [9-13], quantum information processing [14], atomic frequency standard [15][16][17][18], and quantum nonlinear optics [19,20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many studies on EIT and related phenomena have been carried out, which reveal the importance of EIT in understanding the fundamental physics involving interactions between light field and resonant medium [4][5][6][7][8]. It has been shown that EIT may have applications in a variety of research topics such as quantum optics with slow photons [9-13], quantum information processing [14], atomic frequency standard [15][16][17][18], and quantum nonlinear optics [19,20].…”
mentioning
confidence: 99%
“…In recent years, many studies on EIT and related phenomena have been carried out, which reveal the importance of EIT in understanding the fundamental physics involving interactions between light field and resonant medium [4][5][6][7][8]. It has been shown that EIT may have applications in a variety of research topics such as quantum optics with slow photons [9-13], quantum information processing [14], atomic frequency standard [15][16][17][18], and quantum nonlinear optics [19,20].Recently, Lukin et al proposed a mechanism to entangle two photons in an EIT medium based on obtaining slow photons at different frequencies [21]. Since the EIT created by a monochromatic field only provides the steep dispersion near the resonant frequency, sophisticated schemes are proposed to obtain slow photons at different frequencies [21,22].…”
mentioning
confidence: 99%
“…9, with beating oscillations observed whichever variable is monitored. This detection approach originally introduced in [53], was refined in [50,51] and discussed in refs [54][55][56]. It allows to reach a higher precision in the clock frequency measurement, as typical of the Ramsey fringes.…”
Section: Dark Resonance Fringes a Pulsed Regime Lineshapementioning
confidence: 99%
“…This operation was inspired by the Ezekiel's group work at MIT on a thermal beam of sodium atoms [53]. While in the standard Ramsey approach, a coherent superposition of clock states in the bare atomic/molecular basis is dynamically produced by a π/2 pulse depending on pulse duration and laser power, the coherent superposition, in the three-level two-photon approach, is created by an optical pumping process long enough to reach a steady-state.…”
Section: Introductionmentioning
confidence: 99%
“…By coupling long-lived states via, but never populating, radiative states, experimenters can emulate near-ideal two-level quantum systems with no significant decay [1][2][3]. This technique has been used to measure sub-linewidth features [4,5] and to construct atomic interferometers which, by exploiting photon recoil, create spatially separated atomic wave packets which are sensitive to gravity [6,7] or fundamental constants [8,9]. The effective two-level system, which emerges from the Raman problem, can exhibit behavior such as Rabi flopping [10,11], can be used for experiments such as Ramsey interferometry [12,13], and can provide the qubits for quantum information processing [14][15][16].…”
Section: Introductionmentioning
confidence: 99%